PEMBINAAN IBU BALITA DALAM PEMBUATAN MAKANAN PENDAMPING ASI MELALUI PROGRAM MOTHER SMART GROUNDING DI DESA TEGAL LINGGAH, KECAMATAN SUKASADA, KABUPATEN BULELENG - Erawati, Ni Ketut; Astini, Ni Nyoman Ayu Dwi; Gozali, Wigutomo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institute Teknologi dan Kesehatan (ITEKES) Bali, 2022)
One of the problems in the health sector that is still experienced today is related to infant nutrition, namely the lack of mother's knowledge about giving MP-ASI, the lack of use of quality local food ingredients for MP-ASI and the large number of instant MP-ASI given by mothers to toddlers, giving MP-ASI that is not suitable for duration, frequency, texture and variations according to age stages. One area that is still experiencing this condition is Tegallinggah Village which has a coverage of 80 children under five and 10 of them are still categorized as undernourished. Moving on from the above problems, it is necessary to follow up to overcome this through an integrated program, one of which is the mother smart grounding program. As the name implies, this activity targets mothers of toddlers where this program consists of a series of educational activities, distribution of booklets and accompanied by demonstrations on the preparation of MP-ASI for toddlers. It is hoped that the implementation of this program can increase the understanding of mothers under five about the preparation of the right MP-ASI for toddlers according to age so that the incidence of stunting can be slowly reduced. The results of this service will see changes in the knowledge of mothers of children under five about nutrition by looking at the differences in the pre-test and post-test scores. With this service activity, it is expected to be able to motivate and increase the creativity of mothers of toddlers in preparing toddler nutrition. Keywords : Mother Smart Grounding, Stunting Nutrition